Phylogenetic evidence of a new canine distemper virus lineage among domestic dogs in Colombia, South America (2014)
ABSTRACT: Canine distemper virus (CDV) is a highly contagious viral disease of carnivores affecting both wild and domestic populations. The hemagglutinin gene, encoding for the attachment protein that determines viral tropism, shows high heterogeneity among strains, allowing for the distinction of ten different lineages distributed worldwide according to a geographic pattern. We obtained the sequences of the full-length H gene of 15 wild-type CDV strains circulating in domestic dog populations from the Aburra´ Valley, Colombia. A phylogenetic analysis of H gene nucleotide sequences from Colombian CDV viruses along with field isolates from different geographic regions and vaccine strains was performed. Colombian wild-type viruses formed a distinct monophyletic cluster clearly separated from the previously identified wild-type and vaccine lineages, suggesting that a novel genetic variant, quite different from vaccines and other lineages, is circulating among dog populations in the Aburra´ Valley. We propose naming this new lineage as ‘‘South America 3’’. This information indicates that there are at least three different CDV lineages circulating in domestic and wild carnivore populations in South America. The first one, renamed Europe/South America 1, circulates in Brazil and Uruguay; the second, South America 2, appears to be restricted to Argentina; and the third, South America 3, which comprises all the strains characterized in this study, may also be circulating in other northern countries of South America.